PENGENDALIAN HIPERTENSI DALAM PEMANFAATAN SUMBER LITERASI KESEHATAN DI PUSKESMAS SIMPANG TIGA KOTA PEKANBARU PROVINSI RIAU - Masfalah, Febri; Saputra, Bayu; Lita, Lita (Jurnal Ilmu Keperawatan, 2023)
Hypertension is not an infectious disease but is one of the causes of premature death worldwide. The effort in hypertension control is done through self-management or the change of lifestyle of the patients, such as dieting, resting, exercising, and taking the medication regularly (hypertension cannot be cured but can be controlled). Utilizing health literacies can increase one’s ability to understand and maintain attitudes toward caring for his health. This research intended to figure out the picture of the efforts in hypertension control by utilizing the health literacy sources in the health center (puskesmas) of Simpang Tiga, Pekanbaru City, Riau province. This research employed a quantitative study with a simple descriptive survey. The total sample was 95 respondents chosen by purposive sampling technique. The data in this research was collected by a questionnaire that passed the validity test. The data analysis was univariate. Univariate tests were age, gender, education, job, and the utilization of health literacy sources to control hypertension. The result of the research showed that the average age was 54-66 years old; 59 respondents (62,1%) were female; people with SMA/senior high school education background were 50 respondents (52,6%); the unemployed people were 66 respondents (69,5%); the effort in hypertension control was performed by 85 respondents (89,5%) of patients with hypertension; and patients who utilize health literacy sources obtained from health center workers were 80 respondents (84,2%). This research is expected to inform patients with hypertension about the importance of the effort in hypertension control.